A cryptic elapid snake persists in the wake of catastrophic wildfires - Mitchell J. Hodgson; Alexandra K. Ross; Yingyod Lapwong; Santiago Cuartas; Bridget Roberts; Owen Price; Jonathan Webb; Nicola Sentinella; Joshua Lee; Shawn W. Laffan; Hugh M. Burley; Finlay McIntosh; et al. (Oryx)
The increased severity and frequency of bushfires accompanying human-induced global warming have dire implications for biodiversity conservation. Here we investigate the response of a cryptic, cool-climate elapid, the mustard-bellied snake Drysdalia rhodogaster, to the extensive Black Summer fires of 2019/2020 in south-eastern Australia. The species is categorized as Least Concern on the IUCN Red List (last assessed in 2017), but because a large part of its range was burnt during the Black Summer and little was known about its ecology, D. rhodogaster was identified as a priority species for post-fire impact assessment. We evaluated three lines of evidence to assess the impact of the Black Summer fires on D. rhodogaster. Habitat suitability modelling indicated that c. 46% of the predicted range of the species was affected by bushfire. Field surveys conducted 9–36 months post-fire and collation of records from public databases submitted 0–24 months post-fire indicated that D. rhodogaster persisted in burnt landscapes. Fire severity and proportion of the landscape that was burnt within a 1,000-m radius of survey sites were poor predictors of site occupancy by D. rhodogaster. Although conclusions regarding the effects of fire on D. rhodogaster are limited because of the lack of baseline data, it is evident that the species has persisted across the landscape in the wake of extensive bushfires. Our work highlights the need for baseline knowledge on cryptic species even when they are categorized as Least Concern, as otherwise assessments of the impacts of catastrophic events will be constrained.